Analisis Ketidakrataan Jalan Menggunakan Aplikasi Smartphone Di Kota Palangka Raya - Devia Devia (Media Ilmiah Teknik Sipil, 2021)
The International Roughness Index (IRI)'s survey is a longitudinal profile survey to determine Roughness Index of road. The purpose of this survey is to provide an overview of road conditions and provide input in optimizing the maintenance and rehabilitation of the existing roads in the city of Palangka Raya. The data used for analysis is IRI’s data from surveys on several roads that represent conditions in Palangka Raya City with the RoadLabPro application on car. The results showed that the Beruk Angis road had an average IRI value of 9 m/km. On the Yos Sudarso road with an average IRI value of 5.06 m/km. On the Tjilik Riwut road section, the average IRI value is 4.53 m/km. On the Beruk Angis road section with conditions of light damage to severe damage. Proper handling of the Beruk Angis road section needs to be considered for road improvement. The Yos Sudarso and Tjilik Riwut roads with moderate conditions and are handled with regular maintenance.